K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

2 tháng 2 2017

\(\left(-m+n-p\right)-\left(-m-n-p\right)\)

\(=-m+n-p+m+n+p\)

\(=\left(-m+m\right)+\left(-p+p\right)+\left(n+n\right)\)

\(=2n\)

Vậy \(\left(-m+n-p\right)-\left(-m-n-p\right)=2n\)

2 tháng 2 2017

\(\left(-m+n-p\right)-\left(-m-n-p\right)\)

\(=-m+n-p+m+n+p\)

\(=\left(-m+m\right)+\left(-p-p\right)+\left(n+n\right)\)

\(=0+0+\left(n+n\right)\)

\(=0+\left(n+n\right)\)

\(=n+n\)

\(=2n\)

Vậy biểu thức (-m+n-p)-(-m-n-p) =2n

25 tháng 8 2016

=Xn- yn

5 tháng 4 2020

=(2a-3)3+(2a-3)2a+3^2-b

=6a-9+(2a)^2-6a+9-b

=6a-6a+9-9+(2a)^2-b

=(2a)^2-b

13 tháng 10 2016

=x2-9-(x+6)2+12

=(x-x-6)(x+x+6)+3

=-12x-36+3

=-3(4x+11)

Ta có: \(L=\dfrac{15\sqrt{x}-11}{x+2\sqrt{x}-3}-\dfrac{2\sqrt{x}+3}{\sqrt{x}+3}\)

\(=\dfrac{15\sqrt{x}-11-\left(2\sqrt{x}+3\right)\left(\sqrt{x}-1\right)}{\left(\sqrt{x}+3\right)\left(\sqrt{x}-1\right)}\)

\(=\dfrac{15\sqrt{x}-11-2x+2\sqrt{x}-3\sqrt{x}+3}{\left(\sqrt{x}+3\right)\left(\sqrt{x}-1\right)}\)

\(=\dfrac{-2x+14\sqrt{x}-8}{\left(\sqrt{x}+3\right)\left(\sqrt{x}-1\right)}\)

 

12 tháng 10 2021

\(=\left(3a-1\right)^2+2\left(3a-1\right)\left(3a+1\right)+\left(3a+1\right)^2\\ =\left(3a-1+3a+1\right)^2=\left(6a\right)^2=36a^2\)

23 tháng 12 2015

=-m+n-p-m-n+m+p


(-m-m+m)+(n-n)+(-p+p)


(-m)+0+0=(-m) 


TICH NHA

23 tháng 12 2015

viết linh tinh